2020
DOI: 10.1016/j.molmet.2020.101088
|View full text |Cite
|
Sign up to set email alerts
|

Intact vitamin A transport is critical for cold-mediated adipose tissue browning and thermogenesis

Abstract: Objective Transformation of white into brown fat (“browning”) reduces obesity in many preclinical models and holds great promise as a therapeutic concept in metabolic disease. Vitamin A metabolites (retinoids) have been linked to thermogenic programming of adipose tissue; however, the physiologic importance of systemic retinoid transport for adipose tissue browning and adaptive thermogenesis is unknown. Methods We performed cold exposure studies in mice and humans and u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Exposing mice or humans to low temperatures increases plasma concentrations of RBP4 and retinol ( Fenzl et al, 2020 ). In mice, this coincides with an elevation of RBP4 mRNA expression in liver ( Fenzl et al, 2020 ), which may indicate increased retinol mobilization from liver into the blood stream for supporting the adaptation to cold. Indeed, mice lacking RBP4 failed to induce thermogenic reprogramming of their subcutaneous adipose tissue, rendering these mice more sensitive to cold and dropping of their body temperature.…”
Section: Rbp4 Loss-and Gain-of-function Induced Pathologies In Micementioning
confidence: 99%
See 2 more Smart Citations
“…Exposing mice or humans to low temperatures increases plasma concentrations of RBP4 and retinol ( Fenzl et al, 2020 ). In mice, this coincides with an elevation of RBP4 mRNA expression in liver ( Fenzl et al, 2020 ), which may indicate increased retinol mobilization from liver into the blood stream for supporting the adaptation to cold. Indeed, mice lacking RBP4 failed to induce thermogenic reprogramming of their subcutaneous adipose tissue, rendering these mice more sensitive to cold and dropping of their body temperature.…”
Section: Rbp4 Loss-and Gain-of-function Induced Pathologies In Micementioning
confidence: 99%
“…Indeed, mice lacking RBP4 failed to induce thermogenic reprogramming of their subcutaneous adipose tissue, rendering these mice more sensitive to cold and dropping of their body temperature. Retinol induced thermogenic gene expression also in human white adipocytes and increased mitochondrial respiration ( Fenzl et al, 2020 ). Thus, elevated retinol mobilization by RBP4 from liver upon the exposure to cold may be required for an adequate thermogenic adaptation of specific white adipose tissues depots in order to maintain body core temperature, which so far has not been formally tested.…”
Section: Rbp4 Loss-and Gain-of-function Induced Pathologies In Micementioning
confidence: 99%
See 1 more Smart Citation
“…Animal (207) and human (208)(209)(210)(211) studies have revealed a differential expression of genes for carotenoid/retinoid-metabolising enzymes in visceral and subcutaneous adipose tissues, which display important differences regarding developmental origin, metabolism, endocrinology, capacity for adipogenesis and the health risk they entail (212,213) . Genetic ablation of different carotenoid/ retinoid-metabolising enzymes and transport proteins results in alterations of adiposity and defects in brown adipose tissue (BAT) thermogenesis in mice (200,214,215) Furthermore, adipocyte functions such as the thermogenic capacity of BAT in rodents are dependent on the animal's vitamin A status (212,214,216) .…”
Section: Carotenoids and Obesitymentioning
confidence: 99%
“…Even if the RBP4 signaling is not entirely deciphered, many publications tend to demonstrate the negative effect of RBP4 on metabolism and how it can be a promising therapeutic target. In addition, a recent study from Fenzl et al showed that RBP4 is critical in humans and mice for adipose adaptative thermogenesis during a cold exposure [ 33 ]. This discovery highlights new perspectives on RBP4 role in adipose tissue and metabolism, maybe not as detrimental as it first appeared.…”
Section: Rbp4mentioning
confidence: 99%